Optimizing Protocol Performance in the Digital Era: A Study of the Integration of Digital Leadership, Change Management, and Personal Competence in the Protocol Scope - Yunita Tri Susilowati; Agustin Nurcahyanti; Gita Sugiyarti (Universitas Kristen Indonesia Toraja, 2024)
This paper aims to determine digital leadership. Change management capability affects human resource performance protocol through personal competencies as intervention variables in local government institutions throughout Central Java. Quantitative methodology is used in this study, and 150 regional head protocols from all regencies and cities in Central Java are involved. The data shall be scrutinized by employing a quantitative methodology via statistical examination, specifically the structural equation modeling - partial least squares (PLS-SEM), which is designed to facilitate path analysis incorporating latent variables. The study results indicate that change management capability and digital leadership significantly impact individual capability and protocol HR performance. It is proven that individual capability functions as a link between two independent variables and human resource performance. In the era of disruption, digital leadership and the ability to manage change are very important to improve protocol adaptability.